Enhancement of HSA-pFSHβ production by disrupting YPS1 and supplementing N-acetyl-L-cysteine in Pichia pastoris - Luo, Gang; Geng, Zijian; Kuerban, Buayisham; Xu, Yingqing; Yang, Jingjing; Liu, Jiying; Li, Muwang (Frontiers in Microbiology, 2022)
Follicle-stimulating hormone (FSH) is an important glycoprotein hormone that is widely used in assisted reproduction technologies and animal husbandry industry. Human serum albumin and porcine FSHβ fusion protein (HSA-pFSHβ) is a promising candidate for long-acting FSH. However, HSA-pFSHβ secretory expression was accompanied by degradation in Pichia pastoris. In this study, we explored the beneficial effect of YPS1 gene disruption and N-acetyl-L-cysteine (NAC) supplementation on the degradation and production of HSA-pFSHβ fusion protein. Our results showed that YPS1 gene disruption reduced the degradation of intact HSA-pFSHβ and increased the yield of intact protein in the culture medium and cells without affecting the integrity of the cell wall. Moreover, the beneficial effects of YPS1 gene disruption were associated with the upregulation of the MAPK signaling pathway and maintenance of redox homeostasis. YPS1 gene disruption and NAC supplementation had synergistic effects on HSA-pFSHβ production. In addition, disruption of vacuolar morphology by YPT7 gene disruption or NH4Cl treatment affected the production of recombinant HSA-pFSHβ protein. Furthermore, YPT7 gene disruption inhibited the processing of α factor signal peptide in high-level produced HSA-pFSHβ strain. In conclusion, our results demonstrated that YPS1 disruption could reduce the degradation of intact HSA-pFSHβ proteins, and synergistically increase the yield of intact HSA-pFSHβ with NAC supplementation. This study provided a valuable reference for the production of long-acting FSH and a viable approach to reduce the decrease of recombinant proteins in P. pastoris.